Acute renal failure: Clinical outcome and causes of death - Barretti, Pasqual [UNESP]; Soares, Vitor Augusto [UNESP] (Marcel Dekker Inc, 1997)
Acute renal failure (ARF) is a frequent complication in hospitalized patients and is strongly related to increase in mortality. In order to analyze the clinical outcome and the prognostic factors in hospital-acquired ARF a prospective study was performed. Data from 200 patients with established ARF during the period of January 1987 through July 1990 were collected. The incidence of ARF was 4.9/1000 admissions. Renal ischemia (50%) and nephrotoxic drugs (21%) were the main etiologic factors. The histologic study done in 43 patients showed: acute tubular necrosis (53%), tubular hydropic degeneration (16%), glomerulopathies (16%), and other lesions (15%). Dialysis therapy was performed in 101 patients. The mortality rate was 46.5% and the most important causes of death were. sepsis (38%), respiratory failure (19%), and multiple organ failure (11%). Higher mortality was observed in oliguric patients (62.9%) than nonoliguric (34.5%) (p < 0.05) and in ischemic renal failure (56.7%) when compared to nephrotoxic renal failure (14.7%) (p < 0.05). As primary cause of death was not associated to the acute renal failure, conclude that acute renal failure is an important marker of the gravity of the underlying disease and not the cause of death.
Keywords: acute renal failure; clinical outcome; mortality; prognosis